IDENTIFIKASI DAN ANALISIS KERUSAKAN JALAN PADA RUAS JALAN SIARAN SAKO KOTA PALEMBANG (Universitas Muhammadiyah Palembang, 2022)
The improvement of business, industry and the economy fields, has made community activitiesincreasingly high. One of the important roads that have become business districts is Jalan Siaran Sako,Palembang City with a road length of ± 1,250 m and a road width of ± 7 m. The road is one of the mainroads of industrial and business centers that are often passed by the community. Due to the large numberof activities carried out, the road that is flanked by the market has been badly damaged. Assessment tofind out the type and level of road pavement damage is searched using the Pavement Condition Index(PCI) method and a visual scale assessment of road performance on road damage that occurs in thesearch field is using the Surface Distress Index (SDI) method. Based on the evaluation and calculationsobtained by the PCI method, it shows that the pavement condition index has a Perfect score of 48%,Good at 4%, Very Good at 4%, Moderate at 16%, Bad at 4%, Very Bad at 4%, and Fail by 20%. Basedon the results of the SDI analysis in segments 1,2,4,5 and 25 of 225 in Severely Damaged, in segments8,13, 16,17,21 and 22 of 75 in Moderate condition, in segments 3 and 23 of 85 in Moderate condition, insegments 7 and 24 of 10 are in good condition and in segments 6,9, 10,11,12, 14,15,18,19 and 20 there isno damage in good condition.